Beyond the Framing Process: An X-Ray of Newspaper Reportage of Conflicts in Northern Nigeria - Garba, Sabiu; Aondover , Eric Msughter (Unisia, 2023)
This study assessed the pattern of news framing of the Ombatse conflict in Nasarawa State from to 2012-2015 in Daily Trust and Leadership newspapers to determine whether the newspapers mediated mayhem through the application of framing ideology. The Ombatse is an Eggon cult-like ethnic group laced with a political agenda formed to influence the structure of power in the state in response to the alleged marginalization of the Eggon people. This study employed four frames to measure the perspective of media reports on the phenomenon. The study used the census sampling technique to select specific dailies over a four-year period. News stories were the unit of analysis, and the data-gathering instrument was a coding sheet. The data established that newspapers reported the conflict predominantly in negative patterns, painting a grotesque picture of the situation, thereby creating more tension in the state, especially during the massacre of over 100 federal security personnel. The study concluded that at the time of coverage, Nigerian newspapers did not mediate through positive framing patterns; instead, they created more tension. The study recommended that, since the role of the media in conflict may either inflame or deflate passion toward the end of conflict, journalists should focus more on positive news reports, especially in a multi-ethnic, complex, and fragile country like Nigeria. Such positivity of media frames is germen in minimizing tension and resolving conflict amid mutual suspicion and fear of denomination.